2006
DOI: 10.1897/05-535r.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of ozonated seawater to marine organisms

Abstract: Ballast water transport of nonindigenous species (NIS) is recognized as a significant contributor to biological invasions and a threat to coastal ecosystems. Recently, the use of ozone as an oxidant to eliminate NIS from ballast while ships are in transit has been considered. We determined the toxicity of ozone in artificial seawater (ASW) for five species of marine organisms in short-term (< or = 5 h) batch exposures. Larval topsmelt (Atherinops affinis) and juvenile sheepshead minnows (Cyprinodon variegatus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…A treatment method under consideration is ozonation, which is being proposed as options for the management of ballast water (Herwig et al, 2006;Jones et al, 2006;Oemcke and van Leeuwen, 2004;Perrins et al, 2006Perrins et al, a, 2006b. Ozone is potentially a convenient disinfectant for shipboard treatment of ballast water as no chemicals need to be stored on ships or made available at ports for ships to use.…”
Section: Chemical (Active Substances)pprocesses/methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A treatment method under consideration is ozonation, which is being proposed as options for the management of ballast water (Herwig et al, 2006;Jones et al, 2006;Oemcke and van Leeuwen, 2004;Perrins et al, 2006Perrins et al, a, 2006b. Ozone is potentially a convenient disinfectant for shipboard treatment of ballast water as no chemicals need to be stored on ships or made available at ports for ships to use.…”
Section: Chemical (Active Substances)pprocesses/methodsmentioning
confidence: 99%
“…According to some authors (Bai et al, 2004;Champ, 2002;Gavand et al, 2007;Gregg and Hallegraeff, 2007;Herwig et al, 2006;Holm et al, 2008;Jones et al, 2006;Perrins et al, 2006b;Smit et al, 2008;Tang et al, 2006a,b;Veldhuis et al, 2006) new future ballast water treatment technologies under development include: (i) mechanical processes/methods: filtration and separation; (ii) physical processes/methods: sterilization by ozone, ultra-violet light, pulsating strobe lights, pressure, ultrasonic's, electric currents, acoustics, heat treatment, mixing, cyclone or hydrotech-drum settling, etc. ; (iii) chemical processes/methods: biocides (menadione, glutaraldehyde, peroxyacetic acid), and advanced oxidants or oxidizing chemicals (ozone by-products as bromine, sodium hypochlorite, and related chlorine compounds, hydrogen peroxide), nitrogen, oxygen depletion, pH, flocculation, etc.…”
Section: Ballast Water Treatment Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooper (2002) indicated that ozone toxicity closely corresponded to total residual oxidants (TRO) rather than residual ozone itself in toxicity tests with various marine microalgae, invertebrates, and vertebrates. Ozone toxicity in seawater is mostly referred to as a function of total residual oxidants rather than as ozone itself (Crecelius 1979;Jones et al 2006).…”
Section: Introductionmentioning
confidence: 99%